Categorias gramscianas: análise a partir de teses e dissertações dos programas de pós-graduação na área de Serviço Social no nordeste (2003 – 2017) - Santos, Rosa Angélica dos (2019)
This dissertation has as object of research the thought of Antonio Gramsci in the production of knowledge constituted by theses and dissertations in the postgraduate in the area of Social Work in the northeast. The objective was to analyze the gramscian categories present in the production of theses and dissertations in Social Work in order to apprehend the discussions undertaken and their due contributions in the reflections for the profession. It starts from the understanding of the importance of gramscian thought dialogue in the theoretical reflections of Social Work. This is a bibliographic and documentary research, of quantitative and qualitative nature guided by the critical-dialectical method for allowing the movement of successive approximations between subject-object. It constituted the empirical field of study and research source, the production of knowledge in the Social Work area, resulting from theses and dissertations. The research universe comprised a total of 189 works with appropriation of gramscinan categories, being 53 theses and 136 dissertations, obtained through the documentary survey in the public domains of the Public Universities (Federal and State) in the northeast. The sample consisted of a total of 20 works from three northeastern federal universities: Pernambuco, Piauí and Maranhão, in which the condition of theses and dissertations defended until 2017 was the main criterion. The bibliographic research allowed to elaborate considerations about the insertion of Gramsci thought in Brazil, to capture the theoretical discussions concerning the categories of State, civil society, hegemony, intellectual and political. These categories were the most frequent during documentary research. The results from the analysis of theses and dissertations, focusing on the use of the above categories, showed a deep articulation between the issues that involve the study objects and also reveal how the gramscian categories present in the different themes are targets for professional investigation and intervention. The documentary research also allowed us to draw an overview of the use of gramscian categories aggregated by theme and the characterization of postgraduate studies in the area of Social Work in the region. The data analyzed reveal the contemporaneity of gramscian thought in the unveiling of social reality complexes, as well as gramscian categories of State, civil society, hegemony, politics, intellectuals and the production of knowledge, conceptual field of research, contribute to thinking particular realities. The theses and dissertations indicate that Social Work has appropriated gramscian thinking in understanding and unveiling the totality of social life.